2014
DOI: 10.4244/eijv9i10a194
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, fate and consequences of ventricular conduction abnormalities after transcatheter aortic valve implantation

Abstract: TAVI-induced new LBBB occurs in almost 40% of patients, almost all before hospital discharge. It occurs three times more frequently after MCS than after ES valve implantation and has a twofold lower tendency to resolve during follow-up. Persistent LBBB is associated with a higher mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 33 publications
2
69
0
2
Order By: Relevance
“…The diagnosis criteria for LBBB were based on the recommendations from the American Heart Association/American College of Cardiology Foundation/Heart Rhythm Society 20 in 4 studies 3,4,13,18 and from the World Health Organizational/International Society and Federation for Cardiology 21 in 2 studies. 11,19 One study 12 did not detail the diagnosis criteria.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis criteria for LBBB were based on the recommendations from the American Heart Association/American College of Cardiology Foundation/Heart Rhythm Society 20 in 4 studies 3,4,13,18 and from the World Health Organizational/International Society and Federation for Cardiology 21 in 2 studies. 11,19 One study 12 did not detail the diagnosis criteria.…”
Section: Search Resultsmentioning
confidence: 99%
“…High heterogeneity was observed (I 2 = 83%, P = 0.001). Self-expandable balloon was a risk of both NOP-LBBB and PPI, 11,18 and we consider that the significant heterogeneity is mainly because the implanted prosthesis differs considerably among studies, as summarized in the Table 1. The main risks for PPI after TAVI include preexistent right bundle branch block, self-expandable prosthesis valve, and depth of implantation.…”
Section: Permanent Pacemaker Implantation In New-onset Persistent Lefmentioning
confidence: 99%
See 1 more Smart Citation
“…Implantation of the Medtronic CoreValve System more frequently led to new lBBB than implantation of the balloon-expandable Edwards SAPIEN valve (53.8% versus 21.7%) with less recovery during follow-up (39.0% versus 9.5%). 36 In the Houthuizen et al 36 study, which had a much longer follow-up than previous trials (median follow-up, 915 days [578-1234 days]), persistent lBBB was also associated with a significant increase in mortality compared with the absence of lBBB and temporary lBBB combined (HR, 1.49; 95% CI, 1.10-2.03; P=0.01). 36 In the GARY registry, the rate of new pacemaker implantation after SAVR was 4.6% as opposed to 23.6% after transfemoral TAVR.…”
Section: Pacing Is a Riskmentioning
confidence: 94%
“…Houthuizen et al [31] reported that approximately 40% of patients developed a new LBBB after TAVR of which most persisted at follow-up, however without the need for pacemaker implantation. In another analysis, a proportion of AV conduction disturbances after the intervention has been shown to recover at 3 months of follow-up, and only 40% of the permanent pacemaker patients for highdegree AV block still had an AV block underlying their paced rhythm [32].…”
Section: Intraventricular Conduction Impairmentmentioning
confidence: 99%